Posterior scleritis following COVID-19 vaccination in an elderly patient - Zeiger, Jennifer Sachs; Negretti, Guy; Shields, Carol L (Indian Journal of Case Reports, 2024)
We report a case of posterior scleritis masquerading as choroidal melanoma following COVID-19 vaccination. An 86-year-old Caucasian male presented to a retina specialist with a 2-month history of blurred vision and pain right eye (OD). He received his fourth dose of the Pfizer-BioNTech COVID-19 vaccine before developing ocular symptoms. An intraocular mass was found OD and he was referred to our Ocular Oncology Service for potential choroidal melanoma with exudative retinal detachment. On examination, there was a 360-degree episcleral injection and no evidence of choroidal mass OD. Multimodal imaging confirmed no abnormality. Previous ultrasonography demonstrated an echolucent choroidal mass, likely representing choroidal effusion and minimal episcleral Tenon’s edema, suggesting posterior scleritis with spontaneous resolution over 1 week. Posterior scleritis following COVID-19 vaccination can masquerade as choroidal melanoma. In our case, the scleritis resolved spontaneously with no treatment and minimal consequences.